Assessing the quality of routine data for the prevention of mother-to-child transmission of HIV: An analytical observational study in two health districts with high HIV prevalence in South Africa. (November 2016) - Nicol, Edward; Dudley, Lilian; Bradshaw, Debbie
Highlights: The study revealed considerable data quality concerns for the PMTCT information. Discrepancies were observed between values on the PMTCT registers and routine monthly report. The point of departure for accurate data transfer is during the collation process. Organisational authorities play a major role in improving data quality. The success of PMTCT in South Africa appear not to have been driven by routine data. Abstract: Background: The prevention of mother-to-child transmission of HIV (PMTCT) is a key maternal and child-health intervention in the context of the HIV/AIDS pandemic in South Africa. Accordingly, the PMTCT programmes have been incorporated in the routine District Health Management Information System (DHMIS) which collects monthly facility-based data to support the management of public-health services. To date, there has been no comprehensive evaluation of the PMTCT information system. Objectives: This study seeks to evaluate the quality of output indicators for monitoring PMTCT interventions in two health districts with high HIV prevalence. Methods: An analytical observational study was undertaken based on the Performance of Routine Information System Management (PRISM) framework and tools, including an assessment of the routine PMTCT data for quality in terms of accuracy and completeness. Data were collected from 57 public health facilities for six pre-defined PMTCT data elements by comparing the source registers with the routine monthly report (RMR), and the RMR with the DMHIS for January and April 2012. This was supplemented by the analysis of the monthly data reported routinely in the DMHIS for the period 2009–2012. Descriptive statistics, analysis of variance (ANOVA) and Bland Altman analysis were conducted using STATA ® Version 13. Results: Although completeness was relatively high at 91% (95% CI: 78–100%) at facility level and 96% (95% CI: 92–100%) at district level, the study revealed considerable data quality concerns for the PMTCT information with an average accuracy between the register and RMR of 51% (95% CI: 44–58%) and between the RMR and DHMIS database of 84% (95% CI: 78–91%). We observed differences in the data accuracy by organisational authority. The poor quality of the data was attributed partly to insufficient competencies of health information personnel. Conclusions: The study suggests that the primary point of departure for accurate data transfer is during the collation process. Institutional capacity to improve data quality at the facility level and ensure core competencies for routine health information system (RHIS)-related tasks are needed. Further exploration of the possible factors that may influence data accuracy, such as supervision, RHIS processes, training and leadership are needed. In particular understanding is needed about how individual actions can bring about changes in institutional routines.